L’enseignement en architecture de paysage en Afrique - Carey Duncan (Projets de Paysage)
This article presents an assessment of landscape architecture education in Africa. It attempts to make the link between educational programmes and recognition of the profession. The profession is only regulated in South Africa, and landscape architecture is currently taught in only a few countries on the continent. Education models are influenced by the French system in the French-speaking countries especially in North Africa, and by the anglo-saxon system, principally from the UK and the USA, in the English speaking parts of the continent. Overall, there has been little adaptation of curricula to take into account specific African contexts, apart from a few adjustments made recently in South Africa. In the light of the review of education programmes that follows, based on the information available to us from the four main regions of Africa (South, North, East and West) and their operating methods, it is clear that little research has been carried out with a view to creating a body of theory specifically for Africa. It would be appropriate to develop an approach integrating local history and adapting vernacular approaches, where appropriate, while retaining an universal analytical and conceptual methodology. To ensure the success of such an endeavour, a collaborative, open-minded approach respectful of indigenous cultures is needed. It would also be highly beneficial to work towards the co-creation of a corpus of literature more relevant to post-colonial Africa in a context of climate change.